Revision arthroplasty after unicompartimental knee arthroplasty - Nike Walter (BMC, 2021)
Abstract Background Unicompartimental knee arthroplasty (UKA) is a promising and increasing application to treat unicompartimental knee osteoarthritis. However, revision arthroplasty numbers after UKA are unknown. Therefore, aim of this study was to determine the nationwide burden of revision after UKA by answering the following questions: (1) How did numbers of revision UKA procedures developed over the last decade as a function of age and gender? (2) How high is the percentage of revision UKA procedures due to infection? (3) Which therapy strategy was chosen for surgical treatment of aseptic revision UKA? Methods Revision arthroplasty rates as a function of age, gender, infection and type of prosthesis were quantified based on Operation and Procedure Classification System codes using revision knee arthroplasty data from 2008 to 2018, provided by the Federal Statistical Office of Germany (Destatis). Results Over the last decade, revision UKA increased by 46.3% up to 3105 procedures in 2018. A trend towards higher numbers in younger patients was observed. Septic interventions constituted 5.7% of all revisions, whereby total procedures increased by 67.1% from 2008 through 2018. The main treatment strategy was an exchange to a bicondylar surface replacement prosthesis, which was done in 63.70% of all cases, followed by exchange to a femoral and tibial shaft-anchored (16.2% of all revisions). Conclusion The increasing number of revision arthroplasty after UKA in Germany, especially in younger patients and due to infection, underlines the need for future efforts to improve treatment strategies beyond UKA to delay primary arthroplasty and avoid periprosthetic joint infection.